2007
DOI: 10.3892/or.17.4.941
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of proliferation and migration of glioma spheroids exposed to temozolomide is less than additive if combined with irradiation

Abstract: Abstract. The aim of this study was to investigate the effect of temozolomide (TZM) in combination with X-rays on proliferation and migration in human glioma spheroids. Multicellular spheroids were derived from GaMg and U87 cell lines. Spheroids were treated with various concentrations of TZM (5 μmol, 0.025 mmol, 0.05 mmol) and irradiation (RT). Proliferation and migration assays were performed. For GaMg spheroids, the proliferation inhibition was 30% (RT), 71%, 79%, 85% (for various TZM concentrations) and 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…We successfully established three-dimensional A549 multicellular spheroids Dose (Gy) Figure 6 Cell survival curves after treatments with radiation alone or combined with 2.5 µg/mL blank composite micelles (radiation alone + blank composite micelles) or doxorubicin (radiation alone + doxorubicin) or doxorubicin-loaded composite micelle (radiation alone + MIX, P , 0.05 for radiation alone + MIX versus radiation alone that are a more physiologically relevant model of lung cancer than monolayer cells, because they resemble the architecture of in vivo tumors 17,25,26 and can recapitulate in vivo processes which may affect drug performance, such as cell-cell contact, variations in the cell cycle, altered metabolism, and diffusion of nutrients, oxygen, or drugs. 17,25,27,28 Multicellular spheroids are relatively easy to produce and maintain in culture, and treatment-related changes in spheroid growth kinetics and tumor cell outgrowth are established and reproducible endpoints. 17,25,29 As a consequence of their particular architectural characteristics, multicellular spheroids have been demonstrated to be extremely useful for testing radiotherapy protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We successfully established three-dimensional A549 multicellular spheroids Dose (Gy) Figure 6 Cell survival curves after treatments with radiation alone or combined with 2.5 µg/mL blank composite micelles (radiation alone + blank composite micelles) or doxorubicin (radiation alone + doxorubicin) or doxorubicin-loaded composite micelle (radiation alone + MIX, P , 0.05 for radiation alone + MIX versus radiation alone that are a more physiologically relevant model of lung cancer than monolayer cells, because they resemble the architecture of in vivo tumors 17,25,26 and can recapitulate in vivo processes which may affect drug performance, such as cell-cell contact, variations in the cell cycle, altered metabolism, and diffusion of nutrients, oxygen, or drugs. 17,25,27,28 Multicellular spheroids are relatively easy to produce and maintain in culture, and treatment-related changes in spheroid growth kinetics and tumor cell outgrowth are established and reproducible endpoints. 17,25,29 As a consequence of their particular architectural characteristics, multicellular spheroids have been demonstrated to be extremely useful for testing radiotherapy protocols.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 However, the spheroid model is a three-dimensional cell culture system that more closely resembles in vivo tumor cell growth and is more physiologically relevant than monolayer cell growth. 16,17 Individual tumor cells growing under these conditions face different microenvironments depending on their position inside the three-dimensional framework of the spheroid.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study by Glicklis et al (Glicklis et al, 2004) has described that hepatocyte spheroids with diameters up to 100 μm have a good oxygenation status. Other studies by Fehlauer et al (Fehlauer et al, 2005;Fehlauer et al, 2006;Fehlauer et al, 2007) have reported that by using glioma spheroids with diameters of 200-250 μm, there are only few hypoxic cells and no central necrosis present.…”
Section: Hypoxia and Tumor Stem Cellsmentioning
confidence: 99%
“…The amount of formazan produced is directly proportional to the amount of LDH in the culture medium, which in turn is directly proportional to the number of dead or damaged cells (Korzeniewski & Callewaert, 1983). The size of spheroids after drug treatment has also been used as a measure of cell viability (Fehlauer et al, 2007;Johannessen et al, 2009;Khaitan et al, 2009;Yamaguchi et al, 2010). Khaitan et al (Khaitan et al, 2009) investigated the effect of the glycolytic inhibitor 2-deoxy-D-glucose on spheroids derived from a human glioma cell line by measuring the size of the spheroids after drug exposure.…”
Section: Spheroids and Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation